INTEGRASI TEORI KINERJA PERUSAHAAN DAN TEORI KEPEMIMPINAN TRANSFORMASIONAL DALAM MENINGKATKAN DAYA SAING ORGANISASI - Adinda, Pramesti Nurul; Hendayana, Yayan (Journal of Applied Accounting And Business, 2025)
This study aims to integrate organizational performance theory and transformational leadership theory as a conceptual framework for enhancing organizational competitiveness in an increasingly dynamic era of global competition. Organizational performance theory emphasizes the importance of operational effectiveness, resource efficiency, and the achievement of strategic objectives as indicators of organizational success. Meanwhile, transformational leadership theory focuses on leaders' ability to inspire, motivate, and transform organizational members to achieve optimal performance through the development of shared vision, empowerment, and intellectual stimulation. The integration of these two theories yields a conceptual model that positions transformational leadership as the primary driving factor for improving organizational performance, which ultimately has implications for enhancing organizational competitiveness. This study employs a conceptual approach by examining relevant empirical and theoretical literature. The analysis reveals that transformational leaders play a crucial role in creating an adaptive and innovative organizational culture, which serves as the principal foundation for sustainable competitive advantage. Thus, the integration of organizational performance theory and transformational leadership theory provides a new perspective in understanding the internal mechanisms of organizations for achieving long-term competitive advantage. This article recommends the implementation of transformational leadership style as a primary strategy in organizational performance development and competitiveness enhancement across various industry sectors.